2017
DOI: 10.1186/s12864-017-4311-4
|View full text |Cite
|
Sign up to set email alerts
|

The insect pathogenic bacterium Xenorhabdus innexi has attenuated virulence in multiple insect model hosts yet encodes a potent mosquitocidal toxin

Abstract: Background Xenorhabdus innexi is a bacterial symbiont of Steinernema scapterisci nematodes, which is a cricket-specialist parasite and together the nematode and bacteria infect and kill crickets. Curiously, X. innexi expresses a potent extracellular mosquitocidal toxin activity in culture supernatants. We sequenced a draft genome of X. innexi and compared it to the genomes of related pathogens to elucidate the nature of specialization.ResultsUsing green fluorescent protein-expressing X. innexi we confirm previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 114 publications
(151 reference statements)
2
37
0
Order By: Relevance
“…Infection by EPNs is the result of a complex process that includes long- and short-range volatile chemical and contact cues, penetration into the host, activation (also known as IJ recovery), release of the symbiotic bacteria, and the release of excreted/secreted nematode proteins (ESPs), which culminates in the death of the host [ 9 , 10 , 19 ]. Activation is a key aspect of the EPN infection process and is required for efficient release of the pathogenic bacteria they carry along with any nematode-derived bioactive molecules that function in killing the host or modulating its immune response [ 7 , 20 , 21 ]. Despite the importance of activation, it has not been well studied among EPNs, nor has it been previously considered as a means of predicting EPN virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection by EPNs is the result of a complex process that includes long- and short-range volatile chemical and contact cues, penetration into the host, activation (also known as IJ recovery), release of the symbiotic bacteria, and the release of excreted/secreted nematode proteins (ESPs), which culminates in the death of the host [ 9 , 10 , 19 ]. Activation is a key aspect of the EPN infection process and is required for efficient release of the pathogenic bacteria they carry along with any nematode-derived bioactive molecules that function in killing the host or modulating its immune response [ 7 , 20 , 21 ]. Despite the importance of activation, it has not been well studied among EPNs, nor has it been previously considered as a means of predicting EPN virulence.…”
Section: Discussionmentioning
confidence: 99%
“…EPN virulence is dependent on its own toxic secretions and/or bacterial symbiont, depending on the species. Certain EPN symbionts have shown attenuated virulence when injected into different insect hosts [ 20 , 21 , 30 ], and the total number of bacterial cells carried by each individual IJ varies from species to species, where, for example, S. carpocapsae IJs carry approximately 40 colony forming units (CFUs) each while S. scapterisci IJs carry approximately 8 each or fewer [ 21 , 31 ]. Therefore, a well-activated nematode is not necessarily lethal to its host, rather the overall virulence depends on the quantity and toxicity of the bacterial symbiont as well as the potency of host immunity, and the toxicity of the nematode-derived excreted/secreted proteins, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The TpsA partner generally has a recognizable N-terminal TPS domain that targets it for secretion through TpsB [ 57 , 60 ]. Kim et al identified three groups of TPS homologues that are widespread in entomopathogens, including PhlA-type hemolysins, contact-dependent inhibition systems, and a third group with an as yet unknown function [ 77 ].…”
Section: Secretion Systems Of Entomopathogenic Bacteriamentioning
confidence: 99%
“…Mcf promotes apoptosis in both insect hemocytes [ 67 ] and mammalian cells [ 68 ], suggesting the mechanism of its toxicity. Several Xenorhabdus species also encode a homolog of McF, which is likely moved through a T1SS [ 77 ].…”
Section: Secretion Systems Of Entomopathogenic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation